A preliminary study of students' knowledge and awareness of covid-19 / Juliana Mohd Abdul Kadir, Nadia Nurul Najwa Mohmad Hassan and Ahmad Naqiyuddin Bakar - Mohd Abdul Kadir, Juliana; Mohmad Hassan, Nadia Nurul Najwa; Bakar, Ahmad Naqiyuddin (Universiti Teknologi MARA Cawangan Pahang, 2021)
COVID-19 outbreaks are widespread globally and became pandemic. This phenomenon erupted in China and became a global health crisis with no sign of stopping. This is not the only time tragedy as in 2003 and 2014, the global panic attacks of SARS-CoV and MERS-CoV have affected the world, respectively. COVID-19 poses serious problem in humans and is fatal. Excessive activity causes many people infected with the virus transmitted. Efforts to plan the best strategy are beneficial if the awareness and attitude towards health and self-control in society is high. Therefore, this study is important to assess students' knowledge and awareness of COVID-19 in Asia country. A total of 265 participants between the ages of 19 and 24 participated in the survey through systematic random sampling techniques. The findings revealed majority of the students interviewed had good knowledge about the issue. The outcome of this research would be in form of a guideline for both scholars and policymakers to plan for further strategies with regards to the precaution of diseases specially COVID-19. Furthermore, this study contributes to theory by providing empirical evidence of the knowledge and awareness of young educated people dealing with health global issue of COVID-19.